Multi-target mechanism of Solanum xanthocarpum for treatment of psoriasis based on network pharmacology and molecular docking - Nilanchala Sahu; Swati Madan; Ramanpreet Walia; Rama Tyagi; Omer I. Fantoukh; Mohammed F. Hawwal; Ali Akhtar; Ibrahim Almarabi; Perwez Alam; Shikha Saxena (Saudi Pharmaceutical Journal, 2023)
Solanum xanthocarpum (SX) has been used to treat a variety of diseases, including skin disorders like psoriasis (PSO). SX possesses many pharmacological activities of anti-inflammatory, anti-cancer, immunosuppressive, and healing qualities. However, the multi-target mechanism of SX on PSO still needs clarity. Materials and methods: The Indian Medicinal Plants, Phytochemicals and Therapeutics (IMPPAT) database and the Swiss Target Prediction online tool were used to find the active phytochemical components and their associated target proteins. OMIM and GeneCards databases were used to extract PSO-related targets. A Venn diagram analysis determined the common targets of SX against PSO. Subsequently, the protein–protein interaction (PPI) network and core PPI target analysis were carried out using the STRING network and Cytoscape software. Also, utilising the online Metascape and bioinformatics platform tool, a pathway enrichment analysis of common targets using the Kyoto Encyclopaedia of Genes and Genome (KEGG) and Gene Ontology (GO) databases was conducted to verify the role of targets in biological processes, cellular components and molecular functions with respect to KEGG pathways. Lastly, molecular docking simulations were performed to validate the strong affinity between components of SX and key target receptors. Results: According to the IMPPAT Database information, 8 active SX against PSO components were active. According to the PPI network and core targets study, the main targets against PSO were EGFR, SRC, STAT3, ERBB2, PTK2, SYK, EP300, CBL, TP53, and AR. Moreover, molecular docking simulations verified the binding interaction of phytochemical SX components with their PSO targets. Last but not least, enrichment analysis showed that SX is involved in several biological processes, including peptidyl-tyrosine phosphorylation, peptidyl-tyrosine modification, and peptidyl-serine modification. The relevant KEGG signalling pathways are the PI3K-AKT signalling pathway, the EGFR tyrosine kinase inhibitor resistance pathway, and the MAPK signalling pathway. Conclusion: The network pharmacology technique, which is based on data interpretation and molecular docking simulation techniques, has proven the multi-target function of SX phytoconstituents.